ANALISIS PENGARUH KOMPENSASI DAN PEMBERDAYAAN KARYAWAN TERHADAP KEPUASAN KERJA SERTA KINERJA KARYAWAN PADA PT PLN (PERSERO) APJ PURWOKERTO - Kusmoro Kusmoro; Achmad Sudjadi (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2013)
This study aims to determine the effect of compensation and employee empowerment on job satisfaction and employee performance at PT PLN (Persero) APJ Purwokerto. This type of research is the type of survey research study conducted in July 2012 with total respondents as many as 76 people. The results showed compensation and employee empowerment have a significant effect on job satisfaction and performance, as well as the variables of job satisfaction is a mediating variable between compensation and employee empowerment on the performance of employees at PT PLN (Persero) APJ Purwokerto. PT PLN (Persero) APJ Purwokerto should make every effort to make employees feel comfortable in work and career as well. Increased compensation can be done with the indirect compensation, such as insurance, benefits, home loan, and others. while empowering employees to be done by giving companies the opportunity to employees to decide and create their own on the job while not breaking the rules